2019
DOI: 10.1016/j.tips.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Understanding the Human Microbiome’s Impact on Pharmacology

Abstract: Our bodies each possess a unique and dynamic collection of microbes and viruses, collectively the "microbiome", with distinct metabolic capacities from our human cells. Unforeseen modification of drugs by the microbiome can drastically alter clinical effectiveness, in the most dramatic cases leading to fatal drug interactions. Pharmaceuticals can be activated, deactivated, toxified, or release metabolites that alter the "canonical" pharmacokinetics of the drug. Predicting and characterizing microbe-drug intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…Emerging evidences have shown that the modification of gut microbiota can drastically alter drug clinical effectiveness (Hitchings and Kelly, 2019). Recently, E. coli infection was observed to significantly reduce the absorption of orally administered enrofloxacin in broilers (Guo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences have shown that the modification of gut microbiota can drastically alter drug clinical effectiveness (Hitchings and Kelly, 2019). Recently, E. coli infection was observed to significantly reduce the absorption of orally administered enrofloxacin in broilers (Guo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…10,11,33,134,135 Microbiota drug metabolism can lead to significant inter-individual pharmacokinetic variability. 136 For example, a strain of Eggerthella lenta capable of inactivating the cardiac glycoside drug digoxin is estimated to inhabit the guts of 40% of the global population. 137 Intestinal degradation of digoxin can lead to higher dose requirements of patients and make selecting a first dose difficult.…”
Section: Prediction Of Microbiome-drug Interactionsmentioning
confidence: 99%
“…Furthermore, the response to the same dose of biologics (mAb) in patients varies greatly due to significant variability in pharmacokinetics (PK), that is, the fate of drugs, including absorption, distribution, metabolism, and excretion in the body . The dosing regimen of biologics is normally selected based on evidence from clinical practice rather than from consideration of their PK and factors influencing individual exposure.…”
Section: Summary and Perspectivementioning
confidence: 99%